Acute and chronic effects of surgical thromboendarterectomy on exercise capacity and ventilatory efficiency in patients with chronic thromboembolic pulmonary hypertension. Issue 2 (1st August 2001) - Iwase, T; Nagaya, N; Ando, M; Satoh, T; Sakamaki, F; Kyotani, S; Takaki, H; Goto, Y; Ohkita, Y; Uematsu, M; Nakanishi, N; Miyatake, K
Abstract : OBJECTIVE: To assess acute and chronic effects of surgical thromboendarterectomy on exercise capacity and ventilatory efficiency in patients with chronic thromboembolic pulmonary hypertension (CTEPH). DESIGN: Cardiopulmonary exercise testing was performed in 20 patients with CTEPH before thromboendarterectomy (baseline), one month after (early phase), and four months after (late phase). Peak oxygen uptake (peakV˙o 2 ) and the ventilatory response to carbon dioxide production (V˙e -V˙co 2 slope) were measured for assessment of exercise capacity and ventilatory efficiency. Right heart catheterisation was performed in all patients before and one month after surgery. RESULTS: Baseline peakV˙o 2 decreased andV˙e -V˙co 2 slope increased along with the increase in pulmonary vascular resistance in patients with CTEPH. After thromboendarterectomy, theV˙e -V˙co 2 slope decreased greatly from baseline to the early phase (mean (SD), 50 (9) to 37 (7), p < 0.05) and reached a steady level thereafter. In contrast, a continued increase in peak V˙o 2 was noted from the early to the late phase (16.9 (4.1) to 21.1 (5.0) ml/kg/min, p < 0.05). The decrease in theV˙e -V˙co 2 slope from baseline to the early phase, but not the increase in peakV˙o 2, correlated strongly with the decrease in pulmonary vascular resistance after surgery ( r  = 0.75, p < 0.01). CONCLUSIONS: Thromboendarterectomy may cause an immediate improvement in ventilatory efficiency, possibly through its beneficial haemodynamic effects. In contrast, exercise capacity may continue to improve towards the late phase, reflecting peripheral adaptation to exercise.